HEALTH COUNSELING ON EARLY DETECTION OF BREAST CANCER "LET'S MAKE SADARI OUR BESTIE" - Purwarini, Justina; Utami, Tuti Asrianti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Breast cancer is one of the biggest health issues for women worldwide. It is a free radical that develops in breast tissue and causes malignant neoplasms that can lead to death in women. Breast cancer is also a malignant disease that begins to attack the cells of the breast. One of the reasons for the rise in breast cancer is the low awareness regarding screening or early detection. SADARI or Breast Self ExaminatSelf-Examinationeasy, inexpensive, effective, and non-invasive method for the early detection of breast cancer, yet it is still not widely recognized and performed regularly. The purpose of this community service activity is to enhance awareness for early screening or early detection to prevent breast cancer by promoting a healthy lifestyle and encouraging self-breast examinations (SADARI) from an early age. The participants in this activity are 76 female high school students from Perguruan Advent Salemba, and they have never participated in similar activities related to Breast Self-Examination. This activity went smoothly and successfully, as evidenced by the increase in the students' knowledge before and after the counseling, and several students were able to perform SADARI practice correctly and well.